PROPAGATION MODEL OF HARMFUL SUBSTANCES AND SENSIBLE HEAT EXCESS IN INDUSTRIAL PREMISES - Besarion Ch. MESKHI; Arkady N. SOLOVYEV; Yury I. BULYGIN; Ludmila N. ALEKSEYENKO; Evgeny I. MASLOV (Advanced Engineering Research, 2010)
An unsteady three-dimensional mathematical model describing processes of convection-diffusion mass transfer of harmful substances and excess heat in the industrial premises with active ventilation is offered. The model takes into account both stationary and mobile sources of pollution and allows to predict  air quality of the working area in the premises of the complicated configuration.